2016
DOI: 10.1039/c6cc06230j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped hollow carbon spheres with a wrinkled surface: their one-pot carbonization synthesis and supercapacitor properties

Abstract: Nitrogen-doped hollow carbon spheres with a wrinkled surface were rationally synthesized for the first time by using graphene oxide as a morphology controlling agent through direct pyrolysis of core-shell structured GO-resol@melamine formaldehyde composites, showing excellent rate performance towards supercapacitors, due to their unique structural and surface properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Simultaneously, doping of N and S with the presence of O efficiently augments the capacitance of carbon material [47]. It is reported that the pyridinic N and pyrrolic N generally are good for the pseudocapacitance, while graphitic N can enhance the conductivity of the carbon material [59,60].…”
Section: Mmentioning
confidence: 99%
“…Simultaneously, doping of N and S with the presence of O efficiently augments the capacitance of carbon material [47]. It is reported that the pyridinic N and pyrrolic N generally are good for the pseudocapacitance, while graphitic N can enhance the conductivity of the carbon material [59,60].…”
Section: Mmentioning
confidence: 99%
“…Porous carbon materials have received tremendous research interest in catalysis, 1,2 energy conversion/storage, 3,4 biomedicine, 5 sensors, 6 and separation 7 due to their high surface areas, porosity, and tailored framework compositions. [8][9][10] In recent decades, porous carbon materials have been extensively synthesized by employing the template approach.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the growing demand for high-rate and high-power batteries, many kinds of high-performance cathode and anode materials have been produced recently [2,3]. Separators are highly important for the performance of electronic products, such as Li-ion batteries, supercapacitors, and so on [4,5,6]. However, separators, critical components of Li-ion batteries, are still being made of polyethylene (PE) or polypropylene (PP) with poor thermal stability and wettability, which raises serious concerns regarding the safety of Li-ion batteries in cases of unusual heat generation [7].…”
Section: Introductionmentioning
confidence: 99%